Islamic-Based Characteristics: Malay Community Model and Education Pattern - Uri, Fatimah; Riadi, Haris; Suprapto, Muhammad; Rajuna, Rajuna (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine the characteristics of Malay society based on Islamic values and the educational patterns that grow and develop within this framework. Malay society shows a distinctive social model, where Islamic teachings are carried out as a belief system and integrated comprehensively into everyday life's cultural, social, and political aspects. To achieve this goal, this study uses a qualitative approach with literature study methods and historical-sociological analysis, which allows for an in-depth exploration of the role of Islam in shaping the patterns of life and education of Malay society. The study results show that Islamic-based education in the Malay community emphasizes the formation of noble morals, internalization of the values ​​of monotheism, and preservation of local traditions in line with the principles of Sharia. This educational pattern strategically maintains the continuity of the community's cultural identity while adapting to changing times' dynamics. Thus, integrating Islamic values ​​into the education system is a significant factor in building individual character and strengthening social cohesion in Malay society.